LEO small satellite payload for CDMA communications (S-band downlink) - Teo, Chee Keong. (2008)
The development of an appropriate multiple access technique has always been a major challenge in satellite communications. Code Division Multiple Access technique (CDMA) with its numerous advantages has become a main candidate for the next generation of mobile land and satellite communication systems. This thesis presents the research and development work done on designing and developing a LEO small satellite S-band downlink payload for CDMA communication. The downlink payload is implemented using the proposed semi- ASIC architecture. This semi-ASIC architecture combines the programmability of a DSP and the low power area overhead of an ASIC. It uses the ASIC for the high throughput functions of the physical layer and the DSP for the low throughput functions of both the physical and the application layers. The final implemented downlink payload consists of a semi- programmable digital baseband processor, which is both power efficient and flexible. In order to reliably transmit the message at S-band, a high performance RF front-end is developed to amplify and upcovert the transmitted signal without distorting much the original signal.